THE MEDIATING EFFECT OF ORGANIZATIONAL COMMITMENT ON THE RELATIONSHIP BETWEEN JOB SATISFACTION AND JOB PERFORMANCE OF PHARMACIST - Hengky Widhiandono; Suyoto Suyoto; Akhmad Darmawan; Ahmad Zainal Abidin bin Abd Razak; Hariyaty Binti Ab Wahab (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
Job satisfaction among pharmacists can give an indication of how well their expectations and the job's rewards match. The objective of this study was to measure the influence of the organizational commitment as the mediation between personality traits, and job performance of the pharmacist in Banyumas Regency. Methods A cross-sectional survey of Banyumas pharmacists was undertaken. Pharmacists were asked to complete a qustionnaire, a 58-item survey that measures the variables: job satisfaction, organizational commitment, and job performance of the pharmacist. Each item can be scored out of a maximum of 5. The linear regression were used to assess effect job satisfaction toward job performance of the pharmacist. Then, the mediation regression model with step causal method were used to assess mediation on effect job satisfaction to job performance of the pharmacist. Key ﬁndings; A total of 160 responses were available for analysis. The majority of study participants were female (72.5%), were work expericence (year) between 1 and 5 years (43.12%), owner’s pharmacy (80.63%) and all worked in pharmacy (100.0%). There was effect job satisfaction toward job performance of the pharmacist. Organizational commitment was found to be a partial mediator in the relationship between pharmacist job satisfaction and performance. Keywords: Job Satisfaction, Organizational Commitment, Job Performance, Pharmacy, Banyumas.